Image in the post-millennium mediation, process and critical tension - Gil, Isabel Capeloa; Bártolo, José 1972-; Gonçalves, Sofia; Alves, Margarida Brito 1972-; Giannetti, Claudia; Silva, Helena Sofia; Caires, Carlos Sena (Onomatopee, 2021)
How does the complex structure of the image today connect to perception, what does this visual culture offer and what is left to the perciever? As we find ourselves in a culture of digital media, wherein Design, Cinema and New Media intersect, this book zooms in on the imagees dynamic factors seen as a field of work in which the creation of contents and forms is inscribed in a post-digital era
Limited edition of 500 copies
This book is supported by DGLAB / Cultura and Camões, IP - Portugual; made possible by FCT - Fundação para a Ciência e a Tecnologia
Keywords: Ästhetik; Bildwissenschaft; Bildtheorie; Visuelle Wahrnehmung; Image (Philosophy); Perception (Philosophy); Mass media / Social aspects; Aufsatzsammlung